Study on the Computed Tomography Dose Index volume (CTDI vol) and CT Mode Relationship in Multislice CT Scan - Fairuz, M.N; Azlinawati, Ali (2014)
The aim of this study was to measure the Computed Tomography (CT) dose at difference scanning modes: helical and axial scanning modes in multislices CT. The CT doses in this study were expressed in a quantity of Computed Tomography Dose Index volume (CTDIvol).The CTDIvol values measurements were determined by using a pencil beam ion chamber (VICTOREEN CT Probes, Model 500-100) with 10cm active chamber on polymethyl methacrylate (PMMA) CTDI headand body phantoms; scanned through multislice CT scan. The dependency of CT dose was investigated on two helical modes; High Quality mode and High Speed mode and three axial modes; one, two and four section modes. In High Quality mode; pitch of 0.75 utilized with the table speed of 3.75, 7.5, 11.25 and 15mm per rotation while in High Speed mode; pitch of 1.5 utilized with the table speeds of 7.5, 15, 22.5 and 30mm per rotation. The values of CTDIvolwere measured at a fixed tube voltage of 120kV, tube current of 150mA and 180mA for head and body scanning respectively. The results showed the High Quality mode gave higher CTDIvol values in which it indicated of higher CT doses delivered compared to High Speed mode with other parameters remain unchanged. The dosedecreases as the table speed and beam collimation increases. At different axial mode; the values of CTDIvolwere approximately same for eachone, two and four section modes. Compared to helical mode, CTDIvol value obtained in axial mode is in between the value obtained in High Quality mode and High Speed mode.